Ultrastructural Changes during the Life Cycle of Mycoplasma salivarium in Oral Biopsies from Patients with Oral Leukoplakia - Mizuki, Harumi; Abe, Ryosuke; Mikami, Toshinari (Frontiers in Cellular and Infection Microbiology, 2017)
Bacteria in genus Mycoplasma spp. are the smallest and simplest form of freely replicating bacteria, with 16 species known to infect humans. In the mouth, M. salivarium is the most frequently identified species. Mycoplasma spp. are parasites with small genomes. Although most of the Mycoplasma spp. that infect humans remain attached to the host cell surface throughout their life cycle, we have previously reported the presence of Mycoplasma salivarium in the epithelial cells of oral leukoplakia and oral lichen planus. However, the mechanism underlying the pathogenicity of M. salivarium has remained unclear. Further studies are needed to identify the process of infection of human cells and the stages in the life cycle of M. salivarium. Electron microscopy (EM) is the method of choice for morphological investigation of Mycoplasma spp. in cells or tissues. This study was performed to clarify and detail the ultrastructure of M. salivarium in tissue biopsies of oral mucosal leukoplakia, using three EM methods: 1) a standard EM processing method; 2) an ultracryotomy and immunolabeling method; and 3) the LR White resin post-embedding and immunolabeling method. This study included five oral leukoplakia tissue samples showing hyperplasia and hyperkeratosis. Although there was some variation in ultrastructural appearances between the three EM methods used, there were four ultrastructural appearances that are believed to reflect the stages of the M. salivarium life cycle in the epithelial cells of the oral mucosa: 1) small, electron-dense cellular-like structures or elementary bodies of M. salivarium; 2) large structures of M. salivarium; 3) M. salivarium organisms in cell division; 4) the sequence of events in the life cycle of M. salivarium that includes: a) elementary bodies of M. salivarium deep in the oral mucosal epithelium; b) replication by binary fission and daughter cell division from the elementary bodies; c) maturation or degeneration of M. salivarium in the epithelial cells mainly in the upper part of the epithelium; and d) death of the organisms in the granular and/or keratinized layer. These ultrastructural images may provide a useful reference for the identification of M. salivarium in diagnostic cytology or biopsy material.